PENGARUH PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR KOMPETENSI PERAWATAN KULIT WAJAH - Ginting, Dewi Sri Rezky (Perspektif Ilmu Pendidikan, 2018)
Generally, facial skin care materials are considered difficult because students are required to be able to remember the steps of facial skin care treatment, therefore, it is important to using instructional models that can help to improve the ability of students in receiving instructional materials. This study aims to determine the effect of instructional model Quantum Teaching on the Basic Skin Care subject as a basic competence of X class Tata Kecantikan SMK Negeri 1 Beringin. This research was conducted by pre experiment methods. This research was conducted at SMK Negeri 1 Beringin in February 2015. The descriptive result of 31 students’ tendency of facial skin care study before being given the application of a quantum teaching (X) model included sufficient category and facial skin care learning after applying Quantum Teaching (Y) including high category. The results obtained showed that there is a significant effect between the results of facial skin care study after being given the application of Quantum Teaching models in students of SMK Negeri 1 Beringin. References Abdurrahman. (2008). Pendidikan bagi anak kesulitan belajar. Jakarta: Rineka Cipta. Deporter, B. (2010). Quantum teaching (Edisi Terjemahan). Bandung: Kaifa. Djamarah, dkk. (2006). Strategi belajar mengajar. Jakarta: Rineka Cipta. Hamalik, O. (2013). Kurikulum dan pembelajaran. Jakarta: Bumi Aksara. Kusantati, H., Dkk. (2008). Tata kecantikan kulit untuk sekolah menengah kejuruan jilid 2. Direktorat Pembinaan Sekolah Menengah Kejuruan Direktorat Jenderal Manajemen Pendidikan Dasar Menengah Departemen Pendidikan Nasioal. Pratiwi, I.K. (2013). Keefektifan model quantum teaching terhadap minat dan hasil belajar bangun datar pada siswa kelas V Sekolah Dasar Negeri Tunon 2 Kota Tegal. Skripsi. Universitas Negeri Semarang. Rakhmawati. (2011). Penerapan model pembelajaran quantum teaching dengan metode diskusi berbantuan lembar kerja siswa untuk meningkatkan hasil belajar materi bentuk pangkat dan akar pada siswa kelas X semester I SMA N Karanganyar Demak tahun pelajaran 2010/2011. Skripsi. Semarang: FMIPA IKIP PGRI. Sudjana. (2012). Metoda statistika. Bandung: Tarsito. Tarigan, D. (2011). Penerapan model quantum teaching untuk meningkatkan hasil belajar mata pelajaran agroindustri pada siswa SMP Negeri 31 Medan. Skripsi. Medan: FT Unimed.